Сriterion for selection of feed additives with different biological effect in the feeding of growing pigs - O. V. Yanovska; Iu. A Gordiienko (Theoretical and Applied Veterinary Medicine, 2023)
To achieve the pork production profitability, it is necessary to eliminate as many unfavorable factors as possible preventing the animal productivity increase. The use of various feed additives is one of the promising directions to assess the state of health and reducing the risks of the development of pathological processes among livestock. The paper presents the results of assessing the effect of feed additives on pig growth performance depending on the initial gut microbiome of healthy store pigs of the large white breed. The composition of the gut microbial population of the experimental animals has been previously assessed, upon which the pigs have been divided into groups. Animals with reduced content of Escherichia coli took BioPlus 2B, with reduced content of lactobacilli – Bacell, with normal ratio of Escherichia coli, bifido- and lactobacilli – Extract SV. The first two drugs are probiotics, the last one is a phytobiotic with antioxidant and antimicrobial properties. Consumption of these additives together with a balanced traditional diet changed the population intestinal microflora composition in favor of Bifidobacterium spp. and Lactobacillus spp., inhibiting the growth of opportunistic pathogenic microflora having favorable effect on animal productivity. The highest increase in the total animal weight has been observed with the consumption of Extract SV (p < 0.01). In the future, it is planned to investigate the effect of drugs with probiotic and antioxidant properties on the productivity indicators of growing pigs under the conditions of simultaneous consumption.